#facialtraumasurgery: Educational Content of Instagram as a Social Media Source for Facial Trauma Surgery. Issue 8 (9th November 2021) - Lentzen, Max-Philipp; Trojtza, Sonja; Zinser, Max; Kreppel, Matthias; Zoeller, Joachim E.; Zirk, Matthias
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: With an uprising influence of social media platforms like Instagram during the last decade, medical and healthcare related posts have accumulated majorly. In particular the head and face characterizes and signifies each individual's human character, which may be the reason why numerous posts are shared on social media platforms. The purpose of this investigation was to assess the content associated with facial trauma surgery and evaluate its educational quality. The authors performed a retrospective investigation on 550 Instagram posts by #facialtraumasurgery due to number of "likes, " comments, type of post, language, its purpose, and source. Furthermore, posts were evaluated due to their educational quality by 3 examiners of different educational levels. The majority of posts showed 0 to 50 "likes" and 0 to 5 comments in English language. The major post type were single photographs (289; 52.5%), multiple photographs (188; 34.2%), videos (73; 13.3%) and predominantly case reports (233; 42.4%). The source was 322 (58.5%) posts by surgeons, followed by 185 (33.6%) clinic posts. Only 10% to 18% of the posts were rated "excellent." Interrater reliability between all 3 examiners presented a high concordance with 89% ( P  = 0.000). Our study presents an analysis of quantity and quality of social media content according to facial trauma surgery. It supports the deduction that most of the content on Instagram is shared by patients and unclear sources and thus is limited informative. Nevertheless, influence of social media on medical information is increasing and practitioners have to face its effect on their patients.